A Non-technical Description of the EGG Real-Time Sound Synthesizer - Manthey, Michael J. (DAIMI Report Series, 1976)
A functioning real-time digital sound synthesizer system, which includes a touch-sensitive 2 1/2 manual keyboard for performance and a screen for interactive development of sounds and registrations, is described. The sound-definition technique allows control over the dynamic aspects of the partial tones, including their individual amplitude and pitch development in time. Both harmonic and inharmonic over- and undertones are a part of the available possibilities. A user-friendly interface which presumes a minimum of knowledge on the part of the user allows these sounds to be distributed arbitrarily over the keyboard together with equally arbitrary scales. Accepted for publication in Computers and the Humanities, 1977.